Matrix-matched iron-oxide laser ablation ICP-MS U-Pb geochronology using mixed solution standards - Courtney-Davies, L.; Zhu, Z.; Ciobanu, C.; Wade, B.; Cook, N.; Ehrig, K.; Cabral, A.; Kennedy, Allen (2016)
© 2016 by the authors; licensee MDPI, Basel, Switzerland.U-Pb dating of the common iron-oxide hematite (a-Fe2O3), using laser-ablation inductively-coupled-plasma mass-spectrometry (LA-ICP-MS), provides unparalleled insight into the timing and processes of mineral deposit formation. Until now, the full potential of this method has been negatively impacted by the lack of suitable matrix-matched standards. To achieve matrix-matching, we report an approach in which a U-Pb solution and ablated material from 99.99% synthetic hematite are simultaneously mixed in a nebulizer chamber and introduced to the ICP-MS. The standard solution contains fixed U- and Pb-isotope ratios, calibrated independently, and aspiration of the isotopically homogeneous solution negates the need for a matrix-matched, isotopically homogenous natural iron-oxide standard. An additional advantage of using the solution is that the individual U-Pb concentrations and isotope ratios can be adjusted to approximate that in the unknown, making the method efficient for dating hematite containing low (~10 ppm) to high (>1 wt %) U concentrations. The above-mentioned advantage to this solution method results in reliable datasets, with arguably-better accuracy in measuring U-Pb ratios than using GJ-1 Zircon as the primary standard, which cannot be employed for such low U concentrations. Statistical overlaps between 207Pb/206Pb weighted average ages (using GJ-1 Zircon) and U-Pb upper intercept ages (using the U-Pb mixed solution method) of two samples from iron-oxide copper-gold (IOCG) deposits in South Australia demonstrate that, although fractionation associated with a non-matrix matched standard does occur when using GJ-1 Zircon as the primary standard, it does not impact the 207Pb/206Pb or upper intercept age. Thus, GJ-1 Zircon can be considered reliable for dating hematite using LA-ICP-MS. Downhole fractionation of 206Pb/238U is observed to occur in spot analyses of hematite. The use of rasters in future studies will hopefully minimize this problem, allowing for matrix-matched data. Using the mixed-solution method in this study, we have validated a published hematite Pb-Pb age for Olympic Dam, and provide a new age (1604 ± 11 Ma) for a second deposit in the same province. These ages are further evidence that the IOCG mineralizing event is tied to large igneous province (LIP) magmatism in the region at ~1.6 Ga.